Cambio climático y migración: actualidad y prospectiva en México y el mundo - Rendón Huerta, Elda Gabriela (2022)
This paper examines the relationship between climate change and the phenomenon of migration. It shows the current situation and forecasts for this phenomenon, which already affects millions of people around the world and is predicted to affect many more soon. This paper focuses on the current situation of climate-induced forced internal displacement in Mexico, which is considered climate migration. It will address the forecasts in this regard for the year 2050, as well as the path that has been followed (and is still not finalized) with the aim of establishing a regulatory framework that will allow the Mexican state to address this increasingly pressing problem.